Satu Rentak - Sunetra Fernando (Wacana Seni Journal of Arts Discourse, 2004)
Petronas Perorming Arts Group's (PPAG) latest offering, Satu Rentak, was performed recently at the Dewan Filharmonik PETRONAS, directed by Mohd. Yazid Zakaria, winner of the best composition award in the Cameronian Arts Award 2003. Satu Rentak represents a first for PPAG in its concert-hall style staging of musical excerpts from the dance-dramas it has produced over the last six years since the group's debut as the DFP's resident cultural body. It also appears that with the emerging presence of Ahmad Muriz Che Rose, finalist in the MPO Forum for Malaysian Composers and the programming of the concert to highlight compositions by PPAG's composers, this musical team is actively taking stock of its musical output.